Effect of project-based learning towards collaboration among students in the design and technology subject - Ibrahim, Dayang Suryati; Mat Rashid, Abdullah (Sciedu Press, 2022)
Teaching Design and Technology that focuses only on the end product had led to students less exposure to collaboration skills in their learning. Therefore, a study that determines the teaching method in applying collaboration skills among students and its effect is required. The two teaching methods used were the ‘doing a project’ method for the control group and project-based learning for the treatment group. A quasi-experimental study was carried out with a nonequivalent control group. Two groups were selected from two different daily schools consisting of 34 students for the control group and 32 students for the treatment group. A pre-test, followed by an intervention for 7 weeks was carried out. After the intervention, a post-test was carried out for both groups. A questionnaire regarding collaboration skills was used in both tests. The data obtained were analyzed descriptively and by inference. The pre-test showed that there was no significant difference in the level of collaboration of both groups. However, the results of the post-test showed that the level of collaboration in the treatment group is significantly higher than in the control group. Thus, the study showed that collaboration can be applied and cultivated among students by using project-based learning. This can be achieved by structured discussion from explicit planning, and student-centered learning activities with teaching and learning aids that support the execution of students’ project work.